Brisingr - Paolini, Christopher (New York : Knopf, 2010)
Eragon tries to uphold the oath he made to save Katrina from King Galbatorix, while being pulled in different directions by the needs of the Varden, elves, and dwarves--all of whom need his help and strength to overcome the tyranny of the king.
Booklist, November 2008
Horn Book, January 2009
Voice of Youth Advocates (V.O.Y.A.), February 2009
Young Adult
Young Adult.
Booklist
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Fantasy; Dragons -- Fiction; Magic -- Fiction; Fantasy fiction; Fantasy fiction